'On my knees': A self-reflexive account of PhD work. - Coelho, J. V. (N/A, 2025)
What is a study for, a book, a doctorate? What is a doctorate in social science for? What is a doctorate in social science for, in Portugal, a semi peripheral country and economy? This self-reflexive, autobiographic research note addresses these questions, by illustrating the intricacies of PhD work as a lived journey and experience.